2014
DOI: 10.1002/ajmg.b.32244
|View full text |Cite
|
Sign up to set email alerts
|

Maternal predictors of anxiety risk in young males with fragile X

Abstract: Children with fragile X syndrome (FXS) demonstrate high rates of anxiety disorders, with 65–83% meeting diagnostic criteria. The severity of anxiety symptoms in FXS has been shown to be partially predicted by elevated negative affect across early childhood (Tonnsen, Malone, et al., 2013). This association suggests that biologically-driven vulnerability emerges early in development, as is reported in non-clinical populations. However, anxiety emergence is likely moderated by multifaceted genetic, biological and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 97 publications
1
5
0
Order By: Relevance
“…Our findings, however, were independent of child problem behavior. Consistent with work demonstrating a relationship between parental stress and child outcomes, we recently reported that elevated parenting stress in mothers with the FMR1 premutation was associated with increased anxiety in their young children, which was also associated with the genetic status of the mother (Tonnsen et al, 2014). Additional research is needed to explore the relationship between maternal responsivity and maternal psychopathology, child psychopathology, and genetic status within this population.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our findings, however, were independent of child problem behavior. Consistent with work demonstrating a relationship between parental stress and child outcomes, we recently reported that elevated parenting stress in mothers with the FMR1 premutation was associated with increased anxiety in their young children, which was also associated with the genetic status of the mother (Tonnsen et al, 2014). Additional research is needed to explore the relationship between maternal responsivity and maternal psychopathology, child psychopathology, and genetic status within this population.…”
Section: Discussionsupporting
confidence: 80%
“…Also, evidence suggests that these effects likely reflect relationships in a subgroup of families and not the entire sample as a whole. Recent evidence supports these hypotheses with elevated behavioral inhibition in young children with FXS (1 to 6 years of age) associated with higher parenting stress that appears rooted in maternal genetic factors with a lower activation ratio associated with elevated parenting stress (Tonnsen, Cornish, Wheeler, & Roberts, 2014). …”
Section: Discussionmentioning
confidence: 94%
“…These data suggest stressors associated with parenting a child with FXS impact both anxiety and MDD with varying time effects. Given the association between maternal stress and well-being to child anxiety in FXS (32), these data underscore importance of attending to psychiatric health in the family of individuals with FMR 1 mutations.…”
Section: Discussionmentioning
confidence: 96%
“…The delivery of a parent-mediated intervention may encourage more positive parent-child interactions and may teach mothers ways to support their children's language development. The indirect effects of interventions that address patterns of parent-child interactions have yet to be examined for children with FXS (Tonnsen, Cornish, Wheeler, & Roberts, 2014).…”
Section: Mothers Of Children With Fxsmentioning
confidence: 99%